1983
DOI: 10.1017/s0033291700051618
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of schizophrenic day-patients at home: an assessment by relatives

Abstract: SynopsisRelatives of 39 schizophrenic patients attending a day hospital in South Glamorgan assessed the patients‘ behaviour at home covering a period of one week. The results pointed to the existence of a sub-group of patients with severe behavioural problems. These patients had had more psychiatric admissions, and had spent a longer total time in hospital. The proportion of forms of behaviour regarded as problems by the relatives themselves was lower than that suggested by their assessments, except in the fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…In writing REHAB, guidelines were provided to cover the possibility that some raters, such as in a day centre, may not have the opportunity to observe some behaviour, such as washing and dressing. Linke and Taylor (1987) point out that in some community settings it is also necessary to interview the spouse, parent or home-help to gather all the relevant information, and Hewitt (1983) has even produced a parallel REHAB scale for assessing patients living at home by interviewing relatives. This latter assessment scale diverges sufficiently from some of the premises and procedures of REHAB as to require validation as a separate instrument.…”
Section: Site Of Administrationmentioning
confidence: 99%
“…In writing REHAB, guidelines were provided to cover the possibility that some raters, such as in a day centre, may not have the opportunity to observe some behaviour, such as washing and dressing. Linke and Taylor (1987) point out that in some community settings it is also necessary to interview the spouse, parent or home-help to gather all the relevant information, and Hewitt (1983) has even produced a parallel REHAB scale for assessing patients living at home by interviewing relatives. This latter assessment scale diverges sufficiently from some of the premises and procedures of REHAB as to require validation as a separate instrument.…”
Section: Site Of Administrationmentioning
confidence: 99%
“…Informal caregiving for people with schizophrenia has proven to have disrupting consequences on carers in both subjective and objective domains (6, 7). Research has shown that about one‐third of the relatives of schizophrenic patients suffer from emotional or behavioural distress (8, 9) and that patterns of familiar interpersonal interaction can worsen the course of schizophrenia (10–12). Many studies have explored carers’ needs and perceptions (13, 14), coping styles (15, 16), mental health (17), quality of life (18) and satisfaction (19).…”
Section: Introductionmentioning
confidence: 99%
“…Case-histories showed clearly, however, that in 4 cases there had been considerable problems in the past. In an earlier study a low degree of burden was found in the relatives of somewhat similar patients at the same day-hospital (Hewitt 1983).…”
Section: Discussionmentioning
confidence: 80%